Analysis of Economic Growth on the Use of Special Autonomy Funds on Papua Poverty - Salmawati; Fikri, Awal; Kopong, Abu Halim (Jurnal Manajemen Bisnis, 2024)
The problem of this research is that economic growth is still minimal, poverty in Warmon village is still quite high, so the research aims to find out the extent to which special autonomy funds influence the level of poverty in Papua and what is the relationship between the level of economic growth and the level of poverty in Papua. This research uses a mixed research method (mixed methods research), namely research based on a combination of positivism and post-positivism. Combination Research is a research method that combines quantitative and qualitative forms. The results show that the special autonomy funds in Papua, especially in the Warmon sub-district, have a positive effect but are not yet optimal because the special autonomy funds are allocated to infrastructure development in the area. The level of economic growth is interconnected and the relationship is tied to the level of poverty, indicating that if economic growth increases then will reduce the level of poverty in Papua, especially in Warmon village.